Principles of managerial finance - Gitman, Lawrence J. (Pearson/Addison Wesley, 2006)
Known for its time-honored, fully integrated learning system, the Eleventh Edition stays on the cutting edge with progressive new tools and fresh, thought-provoking content. Gitman's proven learning goal method artfully weaves together pedagogy with concepts and practice, providing students with a road map to guide them through the content. This revision brings new examples, new pedagogical features, and an increased emphasis on the ethical implications of financial decisions, adding currency and depth to the text's effective, consistent framework for learning. The new focus on ethics explores such provocative topics as trusting bond raters and ethical accounting practices.